The Effectiveness of Integrated Growth Monitoring and Nutritional Surveillance for Early Detection and Prevention of Malnutrition in Early Childhood: A Literature Review - Agung Prihanggara, Dimas; Handini, Laksmi Suci (Journal of Diverse Medical Research: Medicosphere, 2025)
Background: Early childhood malnutrition is a significant public health problem, especially in developing countries. Its impact is not only limited to impaired physical growth, but also affects cognitive development, increases susceptibility to disease, and decreases future productivity. Early detection and effective prevention are essential to reduce the long-term impact of malnutrition and improve the quality of human resources. Growth Monitoring and Nutritional Surveillance are two key strategies in the fight against malnutrition. Growth Monitoring involves monitoring children's growth at regular intervals through weight weighing, height measurement, and nutritional status assessment, while Nutritional Surveillance focuses on collecting, analyzing, and interpreting nutrition data to monitor the nutritional status of the population and identify risk factors that contribute to nutritional problems. Objective: To assess the effectiveness of integrated Growth Monitoring and Nutritional Surveillance in detecting and preventing early childhood malnutrition. Methods: The method used was a literature review from various sources, including scientific journals, reports from health organizations, and government publications with a boundary of 2018-2024. Results and Discussion: The results and discussion show that the integration of Growth Monitoring and Nutritional Surveillance provides a comprehensive and effective approach. Growth Monitoring enables early identification of children at risk of growth disorders, while Nutritional Surveillance provides data on the prevalence, trends, and determinants of malnutrition for targeted interventions. Conclusion: The integration of Growth Monitoring and Nutritional Surveillance is essential to improve the effectiveness of early detection and prevention of malnutrition in early childhood.